Cross-cultural industrial organizational psychology and organizational behavior: A hundred-year journey. - Gelfand, Michele J.; Aycan, Zeynep; Erez, Miriam; Leung, Kwok (Journal of Applied Psychology, 2017)
and beyond. (PsycINFO Database Record